Experimental evaluation of thermo-mechanical performances of candidate rocks for use in high temperature thermal storage. (1st June 2016) - Tiskatine, R.; Eddemani, A.; Gourdo, L.; Abnay, B.; Ihlal, A.; Aharoune, A.; Bouirden, L.
Highlights: Rock performances evaluation for use in high temperature TES applications. Rocks thermo-mechanical behavior during thermal cycling and parameters influencing their lifetime have been discussed. Empirical equations were developed for estimation of rock hardness. Carbonated, foliated and coarse-grained rocks are unsuitable for high temperature thermal storage. Rhyolite showed excellent ability for use in high temperature TES. Abstract: Packed-bed of rocks using air as heat transfer fluid (HTF) are identified as a promising alternative and cost effective solution for thermal energy storage (TES) in concentrating solar power plants (CSP). Desert sands, igneous and other rocks are being intensively tested for heat storage at high temperature. This paper focuses on the study of several candidate rocks for heat storage. Thirteen samples are collected from diverse places in Morocco and thermally cycled between 20 °C and 650 °C. The chemical and thermo-physical properties influencing the lifetime of rocks are identified. Vickers hardness test has been used to evaluate the compressive strength of the samples and the effect of thermo-mechanical stress during thermal cycling. The obtained results show that quartz and calcite are the principal minerals controlling rock physical properties. Limestone, marble and granite have not withstood thermal cycling. Their hardness decreases after each cycle. Rhyolite and quartzitic sandstone show excellent ability during thermal cycling. When comparing their principal characteristics, rhyolite seems to be the most promising candidate for high temperature TES.